مغل دور زوال میں حکمرانوں اور مشائخ نقشبندیہ کے باہمی تعلقات و روابط کا تحقیقی مطالعہ : "The Mutual Relations between the Mughal Rulers and the Naqshbandi Sufis during the Decline of the Mughal Empire: An Analytical Study" - Qurat ul Ain Fozia; Dr. Hafiz Abdul Majeed (Al Manhal Research Journal, 2025)
The decline of the Mughal Empire in South Asia was marked by political instability, weak leadership, and internal conflicts. During this period, the relationship between the Mughal rulers and the Naqshbandi Sufis became a significant factor in shaping the socio-political and religious landscape of the region. The Naqshbandi order, known for its emphasis on spiritual discipline and reform, engaged with the Mughal rulers in matters of governance, morality, and public guidance. This research study investigates the mutual relations between the declining Mughal authority and the Naqshbandi Sufis, analysing how spiritual influence, moral advice, and socio-religious activism contributed to sustaining or challenging imperial policies. By examining historical sources, this study highlights the role of Sufi–ruler interactions in the transitional phase of the Mughal Empire and their impact on Muslim society in South Asia.